Pengembangan Media 3D Materi Indera Pendengaran Manusia dengan Augmented Reality Assembler Edu - Shofaul Hikmah; Mohammad Kanzunnudin; Khamdun Khamdun (Departement of Mathematics Education, 2023)
The purpose of this study was to analyze the needs, analyze the feasibility and effectiveness of 3D learning media material for the sense of human hearing with Augmented Reality Assemblr Edu students of class IV MI at KKG MI Sedan District, Rembang Regency. This research is research development or Research and Development (R&D) using the Borg and Gall development method Qualitative data analysis is used to analyze how teachers and students respond in carrying out 3D learning with Augmented Reality Assemblr Edu to improve understanding of the material sense of human hearing. Data from the questionnaire were analyzed quantitatively. Based on the results of interviews, questionnaires, and observations made, it can be concluded that the level of need for 3D learning media for human hearing senses with Augmented Reality Assemblr Edu is quite high. The results of the development of this media have been tested for effectiveness with the results of accumulated scores by 3 material validators, namely 53.51 and 52 out of a maximum score of 60. An average of 87% was obtained from material expert validators. The accumulation of media expert validators is 67.70 and 71 with a maximum score of 80 obtained an average percentage of 85.2%. The accumulation of user experts, namely 16.15 and 17, out of a maximum score of 20, obtained an average percentage of 81.64%. So that all three are included in the criteria of